Hukum Menyusui bagi Ibu Pecandu Narkoba Ditinjau dari Perspektif Maqashid al-Syari’ah - Fitriani Fitriani (Ar-Raniry: International Journal of Islamic Studies, 2019)
Breastfeeding is a mother's nature, but in a mother's condition as a drug addict, it can endanger her baby because drugs can be excreted into breast milk. This is the problem and the purpose of this study is how the law of breastfeeding drug addicts mother both from a medical perspective or a review of maqāshid al-syarī’ah.  This research uses qualitative research methods that are descriptive in nature, namely a research method that aims to form a clear, systematic, factual and accurate picture of breastfeeding and the dangers of breastfeeding being contaminated with drugs. The type of research used is library research (library research), which is collecting data or scientific work in accordance with the object of research or collection of library data to solve a problem which basically rests on a critical and in-depth study of relevant library materials. The results showed that if the mother is a drug addict, breastfeeding is prohibited, in this case sadd al-żarī‘ah takes a role because breastfeeding is a means (wasilah) for the entry of drugs into the body. babies, whereas from medical science it is explained that babies who are exposed to drugs through breast milk cause symptoms of poisoning, withdrawal and have the potential to affect cognitive development when they are adults. Al-kulliyat al-khams sees something that is a primary need (dharuriyyah) in a child who is still an infant is keeping the child physically healthy (hiifz al-nafs) and reason (hifz al-aql) as for the benefit by continuing to provide breast milk so that the baby's nutrition is fulfilled in that condition is a secondary need (hajiyyah). So the stipulation of haram law based on sadd al-żarī'ah about breastfeeding for drug addicts mother is in line with maqashid asy-syari‘ah, namely to protect the soul (hifz al-nafs) and reason (hifz al-aql).